2014
DOI: 10.1002/ejlt.201300460
|View full text |Cite
|
Sign up to set email alerts
|

Influence of industrial physical refining on tocopherol, chlorophyll and beta‐carotene content in sunflower and rapeseed oil

Abstract: The main purpose of this article was to investigate the influence of individual processes in physical refining on tocopherol content in sunflower and rapeseed oils. During refining some chemical parameters, the oxidative stability of oils and some minor compounds such as chlorophyll and betacarotene, were determined. Those analytical data with explained chemical backgrounds gave more qualitative overview of what happened to the same lot of oils being processed in a continuous operation. Some processes were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 27 publications
4
76
3
3
Order By: Relevance
“…The presence of high levels of free fatty acids, or free acidity, is due to wet harvest conditions which promote the action of lipases generating these molecules, as well as moist grains during storage (Beratlief and Iliescu, 1997). In sunflower oil FFA varied from 1.19 to 1.35% (w/w) in regular sunflower oil (Kreps et al, 2014), from 0.76 to 1.13% in HOHPSO (Marmesat et al, 2008) and can reach up to 4% in HOSO (Moschner and Biskupek-Korell, 2006). FFA are neutralized during the refining process in order to reduce their undesirable effects as undesirable flavor.…”
Section: Free Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of high levels of free fatty acids, or free acidity, is due to wet harvest conditions which promote the action of lipases generating these molecules, as well as moist grains during storage (Beratlief and Iliescu, 1997). In sunflower oil FFA varied from 1.19 to 1.35% (w/w) in regular sunflower oil (Kreps et al, 2014), from 0.76 to 1.13% in HOHPSO (Marmesat et al, 2008) and can reach up to 4% in HOSO (Moschner and Biskupek-Korell, 2006). FFA are neutralized during the refining process in order to reduce their undesirable effects as undesirable flavor.…”
Section: Free Fatty Acidsmentioning
confidence: 99%
“…Topkafa et al (2013) found that chlorophyll varied from 403 to 1021 ppb in four crude sunflower oils and β-carotene varied from 1692 to 2803 ppm. The refining process reduces the chlorophylls content up to 96% and 80% the β-carotene content (Kreps et al, 2014).…”
Section: Colorantsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of cold-extraction these pigments permeate to oil from seeds in amounts depending on the seed species, environmental conditions, degree of seed maturity, or the storage process. They affect the color of the oil, which is one of the basic quality characteristics of the obtained product, thereby affecting consumer preferences, while they often make the decision to purchase on this basis [12][13][14]. Concerning the content of chlorophyll in seeds, at full maturity stage it usually amounts to 1-2 ppm, while in the case of physiologically matured seed (35 days before maturity) it can be as high as 1,239 ppm [15].…”
Section: Introductionmentioning
confidence: 99%
“…The refining has a positive effect on the oxidative stability of the oil. According to Kreps et al (2014), the refining process removes 79.2% of hydroperoxides from crude oil. Nzikou et al (2009) and Anwar et al (2007) reported peroxide values of 1.67 and 1.27 meq/kg of soybean oil, respectively; these values are lower than those obtained in the present study.…”
Section: Physicochemical Properties Of the Crude And Refined Oilsmentioning
confidence: 99%